Coexistence of asthma and obstructive sleep apnea - Alicja Andrzejak; Hubert Olszewski; Marcin Walter; Kacper Stolarek; Mateusz Szarek (Nicolaus Copernicus University in Toruń, 2024)
Obstructive sleep apnea (OSA) and asthma are common respiratory diseases that can coexist in the same patient. Epidemiological and pathophysiological data suggest an independent association between the two diseases. Over the past few decades, a wealth of data has emerged on the prevalence of asthma and OSA. The prevalence ranges from 38% to as high as 70%.